Isolation of potent alpha-glucosidase inhibitor from a novel marine bacterium Arthrobacter enclensis - Mawlankar, Rahul B.; Dharne, Mahesh S.; Dastager, Syed G. (SN Applied Sciences, 2020)
Alpha-glucosidases are involved in the hydrolyzation of glycosidic bond of di- or oligo-saccharides into mono-saccharides, thus help in the breakdown and absorption of sugars. Inhibition of alpha-glucosidases by inhibitors tend to slow break down and release of sugars into the bloodstream and can be used as therapeutic agents in the treatment of diabetes and obesity. In particular, some of the inhibitors are used in the treatment mainly acarbose, voglibose, and miglitol. In this study, we have reported the alpha-glucosidase inhibitory compound from a newly described marine bacterium Arthrobacter enclensis. The purified compound from A. enclensis was identified by HPLC, and further FTIR and tandem mass spectrometry (MS/MS) methods. The purified compound was annotated and identified by a Web tool CFM-ID (Competitive Fragmentation Modeling for Metabolite Identification). From analysis it was found that the compound showed high similarity with acarbose which is a C7N aminocyclitol compound. Further, we analyze the draft genome of A. enclensis using anti-SMASH. We observed that it matches the homology with biosynthetic gene cluster of acarviostatin and acarbose with 11% and 7% respectively. We demonstrated that, the purified compound from A. enclensis shows the inhibitory activity against alpha-glucosidase with an IC50 value of 500 ± 0.142 μg/ml as compared to standard acarbose, which showed an IC50 value of 200 ± 0.012 μg/ml. This result suggests that A. enclensis has a tendency to produce a C7N aminocyclitol like molecule which matched to acarbose and it uses different biosynthetic gene cluster for the synthesis of C7N aminocyclitol like molecule, which can be further used for the production and treatment purpose.